Identification of immunogenic proteins from Burkholderia cepacia secretome using proteomic analysis - Mariappan, V.; Vellasamy, K.M.; Thimma, J.S.; Hashim, Onn Haji; Vadivelu, J. (2010)
Burkholderia cepacia is an opportunistic human pathogen associated with lung infections. Secretory proteins of B. cepacia are known to be involved in virulence and may mediate important host-pathogen interactions. In the present study, secretory proteins isolated from B. cepacia culture supernatant were separated using two-dimensional gel electrophoresis, followed by Western blot analysis to identify the immunogenic proteins. Mice antibodies raised to B. cepacia inactivated whole bacteria, outer membrane protein and culture filtrate antigen detected 74,104 and 32 immunogenic proteins, respectively. Eighteen of these immunogenic proteins which reacted with all three antibodies were identified and might be potential molecules as a diagnostic marker or a putative candidate vaccine against B. cepacia infections. (C) 2009 Elsevier Ltd. All rights reserved.